Laser Radar Based Autonomous Mobile Robot Guidance System for Olive Groves Navigation - Penizzotto Bacha, Franco Victor (2015)
This paper proposes a control strategy for a mobile robot for precision agriculture. The controller allows autonomous navigation through corridors formed by plants or fruit vines and olive trees. Furthermore, a rotation strategy based on odometer is proposed. The controller uses an algorithm for estimating the states of the system based on information from a laser sensor, which is enhanced by an Extended Kalman Filter which considers the model of the robot-environment interaction. The controller also incorporates the use of odometer sensors for automation of rotation between the end and beginning of plant corridors. The method has been tested in a real environment using a Pionner3AT (outdoor) robot navigating over a typical olive grove of the INTA - EEA San Juan (Pocito, San Juan, Argentina).